LEGALIZATION OF ILLEGAL PROCEEDS. SUBJECTIVE COMPOSITION (THE MODEL BASED ON DIRECT INTENTION) - Shashiashvili, Giorgi (European Scientific Journal, ESJ, 2014)
Subjective composition of legalization of illegal proceeds is related to the fact that an individual acknowledges the character of his/her actions and, what is of utmost importance, he/she is well informed about the illegal origin of monetary resources and other property; in other words, he/she purposefully legalizes proceeds. This issue is not solved in the legislations of foreign countries. Three models of the subjective side of an action can be pointed out by generalizing different approaches: the model that is based on direct intention, the model that includes indirect intention, the model that takes into consideration imprudence. This article deals namely with the model based on direct intention.